Pengembangan Sistem Informasi Monitoring Dan Pembayaran Jasa Perbaikan Komputer (Studi Kasus: Cv Mitra Solusi Gresik) - Adithia Risma Rara Putri; Issa Arwani; Welly Purnomo (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2022)
CV Mitra Solusi is a company engaged in services in repairing computers, printers, cctv, banking tools and others. Within one day CV Mitra Solusi made repairs for more than ten customers. Not infrequently, CV Mitra Solusi is flooded with computer repair service rentals. This is what lies behind the problems that exist in CV Mitra Solusi. On the external side, sometimes many customers experience anxiety because they do not know the progress of the ongoing repair work process. So far, customers often ask about repair progress and pick-up times only by telephone. Of course this is considered less effective if the number of repair queues is dense. Another problem faced is the lack of payment options and payments are still manual. Not infrequently payments are hampered because of money change problems or the payment confirmation process that takes time. This research develops a monitoring and payment system for computer repair services to overcome these problems. System development is carried out using the waterfall method with 18 use case diagrams, 18 activity diagrams, 16 sequence diagrams, 11 class model class diagrams and 14 class controller class diagrams, 19 user interface designs, 9 tables modeled on the Physical Data Model (PDM). In implementing the system, the MySQL DBMS is used with the PHP programming language and Laravel 8 is used, the system is integrated with the Midtrans payment gateway and the Whatsapp API. There are 3 tests, black-box testing gets 100% valid results, Compatibility testing gets the system results are compatible, but there are some major issues and minor issues. The results of the Usability Testing (NUA) obtained a final score of 81% which means the system is very feasible.